The Impact of Store Atmosphere and Product Variation on Customer Preference : Study at Tjap Djajakarta Cafe Malang - Fikri, Hanif; Rachmi, Asminah; Zaini, Achmad; Rusdi, (International Journal of Scientific Research and Management (IJSRM), 2024)
Nowadays, cafés are a highly saturated business, especially in Malang City. Due to the high number of café options, customers tend to choose cafés that suit their preferences. Therefore, coffee shop owners must maximize many aspects of their cafés, such as store atmosphere and product variation. These variables are being implemented in Tjap Djajakarta café Malang.This quantitative research involved distributing questionnaires directly to customer of Tjap Djajakarta café who have made purchase. Purposive sampling was used, and data were analyzed using multiple linear regression (Y = a + b1X1 + b2X2+ e) and hypothesis testing.The findings shows that store atmosphere have partial influence to customer preference while product variation doesn’t. Collectively, both variables contribute 37, 8 % influence to customer preference with 62, 2% is influenced by other variables.The study concluded that only store atmosphere variable that significantly influence customer preference.  Tjap Djajakarta café is suggested to explore more variation in their menu especially main course. Furthermore, Tjap Djajakarta also suggested to enhance the product aesthetic especially for coffee product by performing latte art.